Induction to teaching profession: Problems of beginner teachers in the Dominican Republic - Juan Francisco Jáspez; Marita Sánchez-Moreno (Arizona State University, 2019)
This article presents the findings of an exploratory-descriptive study, with a quantitative-qualitative approach, whose objective was to identify and describe the problems faced by beginner teachers who participated in a teaching induction program (INDUCTIO) in the Dominican Republic. Two ad hoc questionnaires were designed and applied to 363 beginning teachers and 45 mentors respectively. Likewise, two focus groups were developed, one with twelve beginning teachers and the other with ten mentors. The findings reflect that management of discipline issues, motivation and the response to students´ individual differences are the problems most faced by beginning teachers. The perception of these problems meaningfully improves after remaining in the program for five months. Furthermore, significant differences are detected regarding the problems identified at the beginning of the program by both novice teachers and mentors. Similarly, significant differences were observed in relation to the problems that the two groups refer to have overcome.